Toxicological issues of conventional gas hydrate inhibitors. (14th December 2021) - Tabaaza, Grace Amabel; Haq, Ihtisham Ul; Zain, Dzulkarnain B.; Lal, Bhajan
Abstract: Gas hydrates formation is a major challenge to effective hydrocarbons flow in pipelines; thus, flow assurance is a remedy. The use of gas hydrate inhibitors is commonly used as an effective method to inhibit gas hydrate formation. This study focuses on the toxicological issues of conventional gas hydrate inhibitors. The study evidence reveals that conventional chemical additives that ensure effective flow assurance are said to contribute significantly to environmental change and damage. This is attributed to their toxicity nature that poses a great environmental risk by such chemical inhibitors; more so thermodynamic inhibitors due to their dissociation ability that affects seafloor stability. This leads to the release of methane (and associated gases) and other toxic components into the column water. However, little is known about the actual toxicity of frequently used gas hydrate inhibitors. This calls for an in‐depth study into such and also the development of greener inhibitors to replace the existing ones.